2019
DOI: 10.4236/oalib.1105722
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Success and Failure Factors of Business Process Reengineering in Africa, Asia, the Middle East, and North America: A Literature Review

Abstract: Using business process reengineering (BPR) to effectively implement new strategic initiatives and integrate new technology can radically upgrade organizations (Dachyar, Yadrifil & Pratama, 2015). The following literature review compares empirical studies from eight different countries (including the United States) to identify global commonalities and differences of Business Process Reengineering (BPR) practices and the Integration of technology in the areas of research interest, critical success factors, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Based on the insights from the literature review on BPR project objectives, approaches, and factors that influence BPR projects and management, open and closed-ended questions were developed. The statements were adapted from previous work and guides on how to capture lessons learned and BPR project success factors in technical organisations, in particular (California Department of Technology, 2017; Project Management Qualification, 2019; Virzi, 2019; Al-Anqoudi et al. , 2021; Harika et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the insights from the literature review on BPR project objectives, approaches, and factors that influence BPR projects and management, open and closed-ended questions were developed. The statements were adapted from previous work and guides on how to capture lessons learned and BPR project success factors in technical organisations, in particular (California Department of Technology, 2017; Project Management Qualification, 2019; Virzi, 2019; Al-Anqoudi et al. , 2021; Harika et al.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the insights from the literature review on BPR project objectives, approaches, and factors that influence BPR projects and management, open and closed-ended questions were developed. The statements were adapted from previous work and guides on how to capture lessons learned and BPR project success factors in technical organisations, in particular (California Department of Technology, 2017;Project Management Qualification, 2019;Virzi, 2019;Al-Anqoudi et al, 2021;Harika et al, 2021). The questions related to project planning, execution, and outcome, including processes and activities involved in a BPR project, establishing a common understanding of the scope of the project, putting the team together with clear responsibilities, leadership qualities, management commitment, resources, and alignment with organisational objectives.…”
Section: Data Collection and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This section attempts to modify Abdolvand et al"s (2008) model of critical success factors (CSF) of PR as shown in figure 4. Abdolvand et al"s model has been used to identify some structure decisions that have been adopted by managers in PrSOs that are known to produce with the implementation of PR (Virzi, 2019). However, the model failed to include the benefits of IT, which is the hallmark of process reengineering, especially in the public sector.…”
Section: Critical Success and Failure Factors Of Pr In Public And Primentioning
confidence: 99%